Mutual Aid and Informal Finance - Elise M. Dermineur; Unathi Kolanisi (The Thinker)
This paper focuses on stokvels in contemporary South Africa. It examines the resilience and persistence of mutual aid in a modern setting. It seeks to build a qualitative model to understand the persistence and adaptation of the stokvels in a modern society where banking institutions coexist with informal credit practices. The concept of cooperation is key to the analysis. We argue that stokvels continue to persist in modern society, despite the rise of banking institutions, because of their cooperative nature.